2018
DOI: 10.1212/wnl.0000000000005607
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of polyphenol intake and the long-term risk of dementia in older persons

Abstract: In this French cohort, a polyphenol pattern provided by a diet containing specific plant products (nuts, citrus, berries, leafy vegetables, soy, cereals, olive oil) accompanied by red wine and tea was associated with lower dementia risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 36 publications
1
40
0
1
Order By: Relevance
“…The 5 earlier prospective observational studies that have examined the relation between flavonoid intake and ADRD risk revealed mixed results ( 26–29 , 49 ). All earlier studies had ≥1 of the following limitations: 1 ) misclassification of flavonoid intakes due to use of flavonoid databases that were incomplete and/or limited to a few flavonoid classes; 2 ) use of an inadequate dietary assessment method, such as a single-day dietary recall, to characterize usual flavonoid intake; 3 ) assessment of diet only at baseline to characterize flavonoid intake over long follow-up periods resulting in regression dilution bias ( 50 , 51 ); 4 ) low statistical power due to small numbers of incident ADRD cases; 5 ) bias due to failure to consider the possible impact of predementia cognitive decline on dietary habits or diet assessment; or 6 ) confounding due to failure to account for overall diet quality because higher flavonoid intakes are associated with healthier diets ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 5 earlier prospective observational studies that have examined the relation between flavonoid intake and ADRD risk revealed mixed results ( 26–29 , 49 ). All earlier studies had ≥1 of the following limitations: 1 ) misclassification of flavonoid intakes due to use of flavonoid databases that were incomplete and/or limited to a few flavonoid classes; 2 ) use of an inadequate dietary assessment method, such as a single-day dietary recall, to characterize usual flavonoid intake; 3 ) assessment of diet only at baseline to characterize flavonoid intake over long follow-up periods resulting in regression dilution bias ( 50 , 51 ); 4 ) low statistical power due to small numbers of incident ADRD cases; 5 ) bias due to failure to consider the possible impact of predementia cognitive decline on dietary habits or diet assessment; or 6 ) confounding due to failure to account for overall diet quality because higher flavonoid intakes are associated with healthier diets ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, among other limitations, incomplete flavonoid assessment was clearly demonstrated by the overall low “total” flavonoid intakes (means of 14.4 and 28.5 mg/d), neither study adequately accounted for overall diet quality, and only 1 of these studies ( 27 ) accounted for the possible impact of impaired cognitive function on the assessment of flavonoid intakes. The 3 studies that failed to observe any associations between flavonoid intakes and ADRD risk ( 28 , 29 , 49 ) only assessed baseline flavonoid intake despite mean follow-up periods of ∼10–30 y. Two of these studies used a single 24-h dietary recall to characterize flavonoid intake ( 28 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total polyphenol intake was calculated as the sum of all polyphenol classes intake from all FV reported by the FFQ. This estimation method has been previously used in other studies [ 25 , 26 , 27 ]. In the Phenol-Explorer database, polyphenol intake was calculated using High performance liquid chromatography (HPLC); however, in the case of lignans and phenolic acids in some FV items (e.g., olives), polyphenol content was calculated using HPLC after hydrolysis, because these treatments are needed to release phenolic compounds that otherwise cannot be analysed [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Diet may have some role as well, since diets rich in foods containing polyphenols with nuts, soy, citrus, berries, olive oil, tea, leafy vegetables and red wine seem to reduce the chance of developing AD [36]. Polyphenols may have some role in reducing bacterial growth in the oral flora and intestinal biome [37].…”
Section: Discussionmentioning
confidence: 99%